A simple spatial model for Edgeworth cycles - Bloch, Harry; Wills-Johnson, Nick (Centre for Research in Applied Economics, Curtin Business School, 2010)
Maskin & Tirole (1998) formalise Edgeworth's (1925) model of a dynamic equilibrium between two players where prices increase sharply and decrease slowly; the Edgeworth Cycle. Here, we present an application of the model, showing how Edgeworth Cycles might arise in a marketplace where spatial competition is important. We illustrate the approach using the example of retail gasoline markets where Edgeworth Cycles have been widely observed.